Seismic discontinuities and subduction zones - Collier, J; Helffrich, G; Wood, B (2001)
The seismic discontinuities at 410 and 660 km depth in the mantle are generally believed to be due to phase transformations in its major component, olivine. An increasing observational base of short-period regional seismic network data supports this view. Here, we analyse cross-sections of discontinuity topography in the northwest Pacific subduction zones to infer the thermal and chemical state of the mantle in a subduction environment. Most of the data is from the southern part of the Izu-Bonin subduction zone. Penetration of the lower mantle by the steeply dipping subducting slab is clearly indicated by depression of the 660 km discontinuity. Elevation of the 410 km discontinuity in this region by up to 60 km implies a thermal anomaly of approximately 900-1000°C relative to the ambient mantle. Observation of the elevated 410 in the seismically active part of the slab indicates that the olivine → wadsleyite phase transformation occurs under essentially equilibrium conditions there, which argues against the transformational faulting hypothesis as the mechanism for deep-earthquakes. Upgoing P-wave reflections from the 410 km discontinuity indicate that it is sharp in the mantle far from subducting slabs. Reflection coefficient variability in and near slabs indicates either a chemical effect or the consequences of topographic focusing. © 2001 Elsevier Science B.V. All rights reserved.